Evaluating federal research programs : research and the Government Performance and Results Act (National Academies Press, 1999)
The Government Performance and Results Act (GPRA), passed by Congress in 1993, requires that federal agencies write five-year strategic plans with annual performance goals and produce an annual report that demonstrates whether the goals have been met. The first performance reports are due in March 2000. Measuring the performance of basic research is particularly challenging because major breakthroughs can be unpredictable and difficult to assess in the short term. This book recommends that federal agencies use an "expert review" method to examine the quality of research they support, the relevance of that research to their mission, and whether the research is at the international forefront of scientific and technological knowledge. It also addresses the issues of matching evaluation measurements to the character of the research performed, improving coordination among agencies when research is in the same field, and including a human resource development component in GPRA strategic and performance plans